Secret Seven on the trail - Blyton, Enid; Ross, Tony (Hodder Children's Books London, 2009)
The Secret Seven are Peter and his sister Janet, Jack, Colin, George, Pam and Barbara. They meet every holiday in the shed at the bottom of Peter and Janet's garden - and solve mysteries, and eat lots of delicious food. But no one can enter the shed without whispering the secret password! There are 15 Secret Seven novels, and a collection of short stories. The Secret Seven have a new meeting place - a treehouse! But someone else is using it too. The gang are furious, but then they learn the intruder is in big trouble, and needs their help. Can the Seven come to the rescue? Each book features rarely seen bonus Blyton: extra stories, a quiz, additional artwork and insights into Blyton's life and writing process